Analisis Strategi Wirausahawan Muda Bidang Multimedia Di Ciputat, Tangerang Selatan - Ali Chaerudin (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
This study aimed to find out marketing strategies undertaken by one of the young entrepreneurs in Ciputat, Tangerang Selatan. Gazza Net which is located in the Sasak Tinggi, Ciputat Subdistrict Kota Tangerang Selatan served as the study sample. Based on the results of the research object in the field, some findings that the pricing strategy of using the method of pricing based on competition based pricing. This is done with a view to offset the price of competitors. When setting a higher price than competitors, then the customer concerned will leave the business, whereas if the price is set less expensive, then worried his business will be bankrupt or insolvent. This is the marketing strategies undertaken by Gazza Net as a young entrepreneur in Ciputat.